Ultrasound diagnosis of Terson syndrome as an indicator of extreme severity in neurocritical care patients - L.A. Mesa Galán; M.A. Henríquez Recine; A. Robles Caballero; S. Yus Teruel; J.R. García Martínez; J.J. Egea-Guerrero; M. Quintana-Diaz (Neurología (English Edition), 2023)
Introduction: Terson syndrome (TS) is defined as any intraocular haemorrhage identified in patients with acute intracranial pathology. TS appears to be associated with clinical severity in patients with subarachnoid haemorrhage (SAH), but the association is yet to be defined in patients with traumatic brain injury (TBI) and intracerebral haemorrhage (ICH). This study aimed to evaluate the diagnostic performance of ocular ultrasound (OU) and its usefulness in clinical practice. Material and methods: We performed an observational, prospective, single-centre study of neurocritical care patients. We analysed cases and controls, defined according to indirect ophthalmoscopy (IO) and OU findings. We determined the diagnostic characteristics of OU. A multivariate analysis was performed to identify clinically relevant associations. Results: The sample included 91 patients diagnosed with ICH (41.76%), SAH (29.67%), and TBI (28.57%). TS was identified by OU in 8 patients (8.79%) and by IO in 24 (24.37%). The adjusted mortality rate in patients with TS showed an odds ratio (OR) of 4.15 (95% confidence interval [CI], 1.52-11.33). All patients with TS detected by OU presented Glasgow Coma Scale scores < 9, with an elevated risk of needing decompressive craniectomy (OR: 9.84; 95% CI, 1.64-59). OU presented an overall sensitivity of 30.43%, specificity of 98.53%, and diagnostic accuracy of 81.32%. For the detection of vitreous haemorrhage, sensitivity and specificity were 87.5% and 98.5%, respectively. Conclusions: OU diagnosis of TS identifies extremely critical patients, who may require the highest level of care; TS is an independent risk factor for in-hospital mortality. Resumen: Introducción: Se denomina Síndrome de Terson (ST) a cualquier tipo de hemorragia intraocular (HIO), identificada en pacientes con patología aguda intracraneal. El ST parece estar relacionado con la gravedad clínica en la hemorragia subaracnoidea (HSA), pero en pacientes con trauma craneoencefálico (TCE) y hemorragia intracerebral (HIC), su asociación está por definir. Diseñamos este estudio para evaluar el rendimiento de la ecografía ocular (EO) y su utilidad en la práctica clínica. Materiales y métodos: Realizamos un estudio observacional prospectivo, unicéntrico en pacientes neurocríticos. Analizamos los casos con respecto a los controles, identificados con oftalmoscopia indirecta (OI), y por EO. Determinamos las características diagnósticas de la EO. Hicimos un análisis multivariante para determinar asociaciones clínicamente relevantes. Resultados: Se incluyeron 91 pacientes con diagnósticos de HIC (41,76%), HSA (29,67%) y TCE (28,57%). El ST fue identificado por EO en ocho pacientes (8,79%) y en 24 pacientes (24,37%) por OI. La mortalidad ajustada para los pacientes con ST tuvo una OR 4,15 con IC 95% (1,52-11,33). Todos los pacientes con ST identificados por EO presentaron una escala de coma de Glasgow <9 y tuvieron un riesgo elevado de precisar craniectomía descompresiva, una OR 9,84 (1,64-59). La EO alcanzó una sensibilidad global de 30,43%, una especificidad del 98,53%, con una precisión diagnóstica de 81,32. Para la detección de la hemorragia vítrea, una sensibilidad y especificidad del 87,5%, y 98,5% respectivamente. Conclusiones: El ST diagnosticado por EO discrimina pacientes neurocríticos de extrema gravedad que pueden requerir el máximo escalón terapéutico y es un factor independiente de mortalidad intrahospitalaria.